1991
DOI: 10.1159/000195889
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis in French Adolescents: Risk Factors and Respiratory Sequels

Abstract: An analysis of the risk factors for pertussis and the possible respiratory sequels was carried out in a sample of 499 children and adolescents aged 10–16 years from the general population in north-eastern France. 44 subjects (8.8%) had pertussis during childhood; and the sex ratio was 1 in these cases. Pertussis was significantly associated with a maternal history of respiratory disease, residence in a rural area and coal heating. In a multiple logistic regression model, a maternal history of respiratory disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Similar findings were reported by others [12,20]; also asthma was significantly more common in children who had had whooping cough before the age of 5 years [20]. Other studies found no evidence for such a longterm effect of pertussis [3,11,12,21]. Although release of histamine and other mediators from human basophils and mast cells plays a significant role in the pathogenesis of respiratory allergy [4] and histamine release from basophils in response to specific allergens can be of great value in the diagnosis of childhood allergic asthma [9], no data on histamine release during pertussis in childhood are available.…”
Section: Introductionsupporting
confidence: 84%
“…Similar findings were reported by others [12,20]; also asthma was significantly more common in children who had had whooping cough before the age of 5 years [20]. Other studies found no evidence for such a longterm effect of pertussis [3,11,12,21]. Although release of histamine and other mediators from human basophils and mast cells plays a significant role in the pathogenesis of respiratory allergy [4] and histamine release from basophils in response to specific allergens can be of great value in the diagnosis of childhood allergic asthma [9], no data on histamine release during pertussis in childhood are available.…”
Section: Introductionsupporting
confidence: 84%